In situ calibration of polar organic chemical integrative sampler (POCIS) for monitoring of pharmaceuticals in surface waters - Vrana, Branislav; Urík, Jakub; Fedorova, Ganna; Švecová, Helena; Grabicová, Kateřina; Golovko, Oksana; Randák, Tomáš; Grabic, Roman (Environmental pollution (Barking, Essex, 2021)
POCIS is the most widely applied passive sampler of polar organic substances, because it was one of the first commercially available samplers for that purpose on the market, but also for its applicability for a wide range of substances and conditions. Its main weakness is the variability of sampling performance with exposure conditions. In our study we took a pragmatic approach and performed in situ calibration for a set of 76 pharmaceuticals and their metabolites in five sampling campaigns in surface water, covering various temperature and flow conditions. In individual campaigns, RS were calculated for up to 47 compounds ranging from 0.01 to 0.63 L d-1, with the overall median value of 0.10 L d-1. No clear changes of RS with water temperature or discharge could be found for any of the investigated substances. The absence of correlation of experimental RS with physical-chemical properties in combination with the lack of mechanistic understanding of compound uptake to POCIS implies that practical estimation of aqueous concentrations from uptake in POCIS depends on compound-specific experimental calibration data. Performance of POCIS was compared with grab sampling of water in seven field campaigns comprising multiple sampling sites, where sampling by both methods was done in parallel. The comparison showed that for 25 of 36 tested compounds more than 50% of POCIS-derived aqueous concentrations did not differ from median of grab sampling values more than by a factor of 2. Further, for 30 of 36 compounds, more than 80% of POCIS data did not differ from grab sampling data more than by a factor of 5. When accepting this level of accuracy, in situ derived sampling rates are sufficiently robust for application of POCIS for identification of spatial and temporal contamination trends in surface waters.
Keywords: léčivé přípravky; Organic Chemicals; organické látky; Passive sampling; kalibrace; Calibration; Sampling rate; chemické látky znečišťující vodu; Water Pollutants, Chemical; Pharmaceutical Preparations; Environmental Monitoring; monitorování životního prostředí; Polar organic contaminants; Aquatic pollution